Association between prognostic nutritional index and prognosis in acute graft-versus-host disease following allogeneic hematopoietic stem cell transplantation: a retrospective cohort study - Li, Gangping; Zhang, Di; Wang, Yongqi; Yuan, Fangfang; Li, Minghui; Fu, Yuewen (Frontiers in Nutrition, 2025)
BackgroundEvidence on the association between prognostic nutritional index (PNI) and prognosis in acute graft-versus-host disease (aGVHD) following allogeneic hematopoietic stem cell transplantation (allo-HSCT) is limited.ObjectiveThis study aims to investigate the relationship between PNI levels and prognosis in patients experiencing aGVHD following allo-HSCT.MethodsWe conducted a retrospective cohort study of patients who underwent allo-HSCT at Henan Cancer Hospital from January 2019 to December 2024. Eligible patients were those diagnosed with aGVHD following allo-HSCT. Data on PNI levels, clinical outcomes, and demographics were extracted from medical records. The primary outcomes were overall survival (OS) and event-free survival (EFS). Multivariable Cox regression and subgroup analyses were performed to assess the relationship between PNI levels and prognosis, adjusting for confounders.ResultsThis study included 109 eligible patients with a mean age of 29.4 ± 15.3 years. Over a 30-month follow-up, there were 69 deaths, 3 relapses/progressions, and 37 survivors. Among the participants, 51 had Grade I-II aGVHD, and 58 had Grade III-IV aGVHD. After adjusting for confounders, the adjusted hazard ratios (HR) for PNI and OS in T2 (35.8–42.5) and T3 (42.5–59.7) were 0.52 (95% CI: 0.23–0.86, p = 0.049) and 0.43 (95% CI: 0.18–0.73, p = 0.013), respectively, compared to individuals with lower T1 (20.2–35.8). For EFS, the adjusted HR values for PNI in T2 (35.8–42.5) and T3 (42.5–59.7) were 0.32 (95% CI: 0.17–0.59, p = 0.026) and 0.31 (95% CI: 0.16–0.56, p = 0.021), respectively, when compared to those with lower T1 (20.2–35.8). These results suggest a potential association between lower PNI levels and poorer prognosis. Kaplan–Meier analysis demonstrated poorer OS (p = 0.047) and EFS (p = 0.078) in the lower PNI group. Subgroup and interaction analyses revealed no significant interactions by age, sex, CD34+ count and ABO match (all p > 0.05), confirming the stability of the association. Sensitivity analyses further supported this consistent association.ConclusionOur study underscores the association between lower PNI levels and poorer prognosis in aGVHD patients following allo-HSCT, emphasizing the need for further research to validate PNI as a reliable prognostic biomarker.